Ecological Features of Large Neotropical Reservoirs and Its Relation to Health of Cage Reared Fish - Carvalho, Edmir Daniel; Silva, Reinaldo José da; Ramos, Igor Paiva; Paes, Jaciara Vanessa Krüger; Zanatta, Augusto Seawright; Brandão, Heleno; Zica, Érica de Oliveira Penha; Nobile, André Batista; Acosta, Aline Angelina; David, Gianmarco Silva (IntechOpen, 2012)
None